Management In Healthcare: Developing A Value Framework For Small Physical Therapy Organizations - Yusupov Sharif Abror Ugli (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Modern healthcare systems are evolving toward higher quality, efficiency, and patient-centered outcomes, leading to a global shift toward value-based healthcare (VBHC). Specific Background: While large healthcare organizations have implemented various VBHC models, small and micro Physical Therapy Primary Healthcare Organizations (PHOs) face unique challenges due to limited resources and structural constraints. Knowledge Gap: Current frameworks inadequately address how small PHOs can measure and operationalize healthcare value in ways that integrate quality, performance, and adaptability. Aims: This study aims to develop a comprehensive Healthcare Value (HV) Framework tailored to the needs of small PHOs, integrating patient-centered, stakeholder-centered, and organization-centered outcomes. Results: Through a scoping review of 74 studies and expert consultations, the proposed HV framework successfully synthesizes healthcare quality, performance outcomes, and organizational capacity for change. Findings show that small PHOs can adopt value-based approaches by optimizing resources, fostering collaboration, and enhancing innovation. Novelty: The integration of “capacity for change” into value assessment represents a novel contribution, addressing dynamic healthcare environments faced by small organizations. Implications: The framework provides a practical guide for small PHOs to align strategic management with patient and stakeholder needs, supporting sustainable healthcare delivery and future digital transformation initiatives.Highlight : The study develops a Healthcare Value Framework specific to small physical therapy primary healthcare organizations. It emphasizes the integration of patient-centered, stakeholder-centered, and organizational outcomes. The framework highlights the role of organizational capacity for change in enhancing healthcare quality and performance. Keywords : Healthcare Value, Physical Therapy, Primary Healthcare Organizations, Value-Based Healthcare, Organizational Capacity